Applications and Theory of Analytic Hierarchy Process - Decision Making for Strategic Decisions 2016
DOI: 10.5772/64042
|View full text |Cite
|
Sign up to set email alerts
|

Combining AHP Method with BOCR Merits to Analyze the Outcomes of Business Electricity Sustainability

Abstract: Over the last three decades, many researchers and decision makers have investigated separately the issues of economic growth, profitability, and quality of life when thinking about business electricity sustainability. The correlations between these paradigms still remain at the stage of discussions, debates, and forecasts as a reaction to the occurred conflicts and disasters. There is a lack of real encryption that demonstrates their interactions. It is useful to materialize the expectations of stakeholders by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Authors suggested the use of SIMUS for estimation because it considers quantitative and qualitative assessment at a single time. Medjoudj et al [6] employed a fuzzy model of decision-making procedure for multi-characteristic problems to measure four different renewable energy sources: solar, geothermal, hydropower, and renewable energy. For ranking the four possibilities in their study, the authors employed a fuzzy analytic hierarchy approach and a fuzzy technique to arrange performance by resemblance to an ideal answer.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors suggested the use of SIMUS for estimation because it considers quantitative and qualitative assessment at a single time. Medjoudj et al [6] employed a fuzzy model of decision-making procedure for multi-characteristic problems to measure four different renewable energy sources: solar, geothermal, hydropower, and renewable energy. For ranking the four possibilities in their study, the authors employed a fuzzy analytic hierarchy approach and a fuzzy technique to arrange performance by resemblance to an ideal answer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, the decision-making process for multi-characteristic problems should be employed to tackle this problem. Some decision-making processes for multicharacteristic problems have been employed in the various literatures for making energy investment decisions, including the Analytic Hierarchy Process (AHP), the Analytic Network Process (ANP), the removal and select transforming actuality and favourite position organisation technique for improvement assessment, multiple objective linear programming, and the Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To examine the various choices, they employed a decision-making practise of multi-criteria, the general index of sustainability, which prioritised economic, environmental, social, and technological considerations. According to Medjoudj et al [14], a practical model was developed in order to shed light on the application of multi-criteria approaches in renewable energy planning. They generated a matrix that calculates the numerous decision-making strategies of multi-criteria that are appropriate for renewable energy planning, as well as their efficacy in doing so.…”
Section: Literature Reviewmentioning
confidence: 99%
“…AHP has been used to do BOCR analysis with various degrees of effectiveness [19][20][21][22][23]. We employ current breakthroughs in the area in our study, utilizing results from critiques of the usage of AHP and BOCR [24].…”
Section: Ahp and Bocr Analysismentioning
confidence: 99%